(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2025)
Today, almost half of the world’s working population are women. Therefore, it is necessary to develop women’s entrepreneurship to ensure the sustainability of business activities. Not only our country, but the whole world is paying great attention to this type of entrepreneurship. The reason is that through the development of women’s entrepreneurship, the unemployed population is provided with a certain level of employment, they have a permanent source of income, and as a result of creating new jobs, they contribute to the development of the countries and the entire world economy.